Optimization of Trehalose Lypids Extraction – Metabolites of Rhodococcus erythropolis Au-1 - Natalya Koretska; Halyna Midyana; Elena Karpenko (Innovative Biosystems and Bioengineering, 2018)
Background. An important task of modern biotechnology is the development of rational technologies for the microbial synthesis of microbial surfactants, in particular, the increasing of the effectiveness of methods for the isolation and purification of microbial surfactants.